Analysis of Faculty Teaching using Multi-criteria Decision Making Approach - Ghosh, Dhrubajyoti; Pal, Anita (International Journal of Engineering and Technology, 2018)
In order to maintain a good standardof any college, the institution should follow paper  based  approach  or  web-based approach  to  gather  student  feedback  on  faculty  teaching to maintain the qualities of the faculty. Students have very much concerned about their teachers who have played a vital role in their life in both outside or inside of the institutions which helps them to justify a teacher and it comes in form of their feedback. In this paper, we introduce a ranking method of the given feedback's factors of teacher's performances with the help of multi-criteria decision making approach using neutrosophic logic.  We  use  the  score   and  accuracy functions  and  the  hybrid  score-accuracy  functions  of single  valued  neutrosophic  numbers  (SVNNs)  and ranking  method  for  SVNNs.